Interaction of papaya seedlings inoculated with different mycorrhizal fungi species - Fontanetti Rodrigues, Maria Gabriela; Marengo Rebeschini, Melina; Arruda Ferreira, Antonio Flávio; Honorato Monteiro, Laís Naiara; da Silva Martins, Maria Eugênia; Dini Andreote, Fernando; de Lourdes Colombo Mescolotti, Denise (Revista Ceres, 2023)
Papaya (Carica papaya L.) is one of the most cultivated fruits in Brazil. Thus, increasing efforts to improve the crop efficiency have been carried out, being the study of quality seedling production of fundamental importance. Arbuscular mycorrhizal fungi, in symbiosis with the root system of plants, can bring great improvements to the morphophysiological aspects of the papaya tree. The aim of this study was to evaluate the interaction of papaya seeds treated with AMF, in order to support management works on the crop. The experiment was installed in an agricultural greenhouse in a completely randomized design with three treatments: T0 – control (no inoculation); T1 - inoculation of seeds with Gigaspora rosea + Gigaspora margarita; and T2 - inoculation of seeds with Rhizophagus clarus, with 40 replicates, with each sowing cell being considered a replicate. Mycorrhizal colonization, seedling emergence and biometric indices at 60 days after sowing were evaluated. High symbiosis rate was observed between papaya seedlings with Rhizophagus clarus and Gigaspora rosea + Gigaspora margarita. Increase in the percentage and speed emergence and decrease in emergence time in relation to control was observed, in addition to increase in biometric characteristics of seedlings, evidencing its beneficial use for higher production.